ANALISIS KUANTITATIF KELENGKAPAN FORMULIR KOHORT IBU DI BAGIAN POLIKLINIK KESEHATAN IBU DAN ANAK PUSKESMAS PORIS PLAWAD TAHUN 2021 - Anas Fajry Rhomadon; Daniel Happy Putra; Lily Widjaja; Puteri Fannya (Journal of Innovation Research and Knowledge, 2023)
Medical records are documentation of identity, examination, treatment, actions, and services that have been provided to patients. Health services during pregnancy must be documented in the mother's card, medical record, mother's cohort, and mother and child health book. The maternal cohort is a collection of data collected from the mother's card. The documentation must be filled in completely because it affects further contact if needed and in certain circumstances, it is required for a medical audit. This study aims to determine the completeness of filling out the mother's cohort form at the MCH polyclinic at the Poris Plawad Health Center in 2021. This study used a quantitative descriptive method. Determining the number of samples using the slovin formula, so that a sample of 68 maternal cohort data was obtained. The results of the research from 68 maternal cohort data obtained an average of completeness of identification (77%), important reports (62%), and procedures for documentation (49%). Factors that influence incompleteness are the absence of an SOP for Filling in the Maternal Cohort, no updating of guidelines, no recording of medical record numbers, less communicative staff, no column for filling in authentication, and double working forms. Suggestions from researchers are to update the guidelines, create SOP Filling in the Cohort of Mothers and carry out outreach, update forms to add authentication records, conduct training/seminars to increase midwifery insights, and devise a workable system of more than 1 person for recording health data in the system.